PENENTUAN DAYA MAKSIMUM PHOTOVOLTAIK DENGAN METODE GROUP - hadi, harsono (Jurnal Sains dan Teknologi Indonesia, 2012)
The maximum power point (MPP) is equivalent to maximum IxV at the I-V curve under G and T conditions. Characteristic and performance of the solar cell, module photovoltaic and solar generator of the photovoltaic system is possible to be evaluated through the MPP. The relationship among model, parameters and constants are expressed by a mathematical model of the exponential equation. Calculation of the MPP value at the intensity irradiation (G) and the cell temperature (T), the maximum voltage (Vmax) are fixed firstly by the current output equal to zero. The voltage output (Vout) is slowly dropped step by step (V=Vmax – n DV, where n = 1, 2, 3, . . . . m) and the current output (I) is founded. The MPPn (Iout x Vout) must be compared to the previous value of the MPPn-1 or MPPn – MPPn-1 ³ 0 Calculating process: the current-voltage (I-V) output, the MPP value is relative complicated and involves measured datum at the various irradiation and cell temperature. To simplifythe calculation of the MPP and I-V output, the group method is used to allocate the each datum [ Gn,Tn, In(In1, In2, In3, . . . Inm), Vn(Vn1, Vn2, Vn3, . . . Vnm), MPPn, Qn, Hn, . . . etc] in its dimensions [ {G1, G2,G3, . . . .Gn}, {T1, T2, T3, . . . .Tn}, {I1, I2, I3, . . . .In}, {V1, V2, V3, . . . .Vn}, {MPP1, MPP2, MPP3, . . ..MPPn}, {Q1, Q2, Q3, . . . .Qn},etc ].